2020
DOI: 10.2147/ott.s234344
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lentivirus-Mediated VEGF Knockdown Suppresses Gastric Cancer Cell Proliferation and Tumor Growth in vitro and in vivo</p>

Abstract: Purpose: Gastric cancer has a high mortality rate worldwide. Although treatments, such as molecular-targeted therapy, have been introduced, the resulting long-term survival and prognosis remain unsatisfactory. Downregulation of the target genes using lentivirus-mediated short hairpin RNA (shRNA) can be an effective therapeutic strategy for patients with gastric cancer. Overexpressed vascular endothelial growth factor A (VEGF) in human gastric cancer cells can be an effective novel therapeutic target for human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Some researchers have demonstrated that VEGF knockdown suppresses tumor cells proliferation. 27 To assess the cytotoxicity of the CHCE/siRNA NPs, the proliferation of SK-MEL-28 cells treated was tested by MTS. The results showed that the CHCE/siRNA NPs had the best anti-proliferation effect on the SK-MEL-28 cells ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have demonstrated that VEGF knockdown suppresses tumor cells proliferation. 27 To assess the cytotoxicity of the CHCE/siRNA NPs, the proliferation of SK-MEL-28 cells treated was tested by MTS. The results showed that the CHCE/siRNA NPs had the best anti-proliferation effect on the SK-MEL-28 cells ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…The PPI network and KEGG results indicated that VEGFA was the main target in the treatment with SZJD against GC. VEGF is a well-known angiogenic factor and plays an important role in the proliferation, migration, and invasion of vascular endothelial cells [ 28 ]. The angiogenic pathway is a sound target for obstructing the excessive proliferation of cells because nutrients and growth factors are supplied through blood vessels to tumor cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic viruses are also relatively simple to generate and they ensure a high level of transgene expression. Many studies were conducted with retrovirus-like particles (RLPs) [209], non-replicative adenoviruses [210] and AAVs [211], whereas other VLPs used for both their capacity to package DNA and their easy retargeting achieved lower transduction efficacy [68,82,212]. Despite several limitationsthe main one being the cytoplasmic delivery of cargos initially addressed to the nucleusnanoparticles (mainly lipid-based) have been extensively used for nucleic acid delivery [213][214][215].…”
Section: Delivery Of Nucleic Acidsmentioning
confidence: 99%